Preparation of tobacco pyrolysis liquids in subcritical/supercritical ethanol and their application in the aroma enhancement of heated cigarettes - Zhao, Xuebin; Zhao, Shengchen; Xu, Yongming; Xu, Heng; Zhang, Zhan; Tian, Haiying; He, Qiang; Ma, Shengtao; Gao, Beibei; Ma, Chengjie (Frontiers in Chemistry, 2024)
The pyrolysis reaction performances of tobacco in subcritical/supercritical ethanol were investigated and the application of tobacco pyrolysis liquids in aroma-enhancing of heated cigarettes was further explored by GC-MS/MS. The reaction temperatures had the most significant impact on the tobacco pyrolysis reaction and higher reaction temperatures promoted the pyrolysis conversion of tobacco, achieving high tobacco conversion and high quantity and content of volatile components in tobacco pyrolysis liquid. The optimal reaction conditions for preparing tobacco pyrolysis liquid were found to be 220 o C, liquid/solid mass ratio=15 and 2 h. The content of ester compounds significantly increased in the tobacco pyrolysis liquid, and the content of nicotine also increased significantly with the increase of reaction temperatures. Sub/supercritical ethanol treatment significantly disrupted the surface structure of tobacco and increased in the degree of tobacco depolymerization with increasing temperatures. The analysis of aroma compounds in the smoke of heated cigarettes indicated that tobacco pyrolysis liquid can significantly increase the release of aroma substances and had a significant aroma-enhancing effect. This article proposed and prepared tobacco pyrolysis liquid in subcritical/supercritical ethanol and explored its potential application in aroma-enhancing of heated cigarettes, offering a new route for aroma-enhancing technology of heating cigarettes.